Comparative ecological and behavioral adaptations of Ovibos moschatus and Rangifer tarandus - Klein, David R. (Rangifer, 1992)
Caribou/reindeer and muskoxen are the only two ungulate species that have successfully occupied arctic tundra habitats. Although confronted with similar environmental constraints, their morphological dissimilarities have enabled them to develop unique behavioral and ecological adaptations that under most circumstances result in minimal overlap in use of forage resources. The large body and gut capacity of muskoxen have enabled them to adopt a strategy maximizing rate of forage intake and energy conservation, whereas caribou/reindeer of substantially smaller body size must pursue selective feeding, requiring high mobility and high energy expenditure. Responses to predators and insects by the two species show similar contrasts in associated energy costs. When confronted with environmental extremes that limit forage availability, competition for food may occur and the resulting differential success is a reflection of their divergent evolutionary routes.